Can I Have Permission to Leave the House? Return Migration and the Transfer of Gender Norms - Michele Tuccio; Jackline Wahba (Institute for the Study of Labor (IZA), 2015)
Does international return migration transfer gender norms? Focusing on Jordan, an Arab country where discrimination against women and emigration rates are high, this paper exploits unique data in which detailed information on female empowerment allows us to construct several measures of discriminatory social norms in Jordan on the role of women, female freedom of mobility, and female decision-making power. Controlling for both emigration and return migration selections, we find that women with a returnee family member are more likely to have internalized discriminatory gender norms than women in households with no migration experience. Further analysis shows that results are driven by returnees from conservative Arab countries, suggesting a transfer of negative norms from highly discriminatory destinations. We also show the implications of our results beyond perceptions for several economic and development outcomes, such as female labour force participation, education and fertility.
Keywords: F22; J16; O15; O53; 330; international return migration; gender inequality; transfer of norms